Influencing factors on the decorative art features of traditional windows and doors in the south Yangtze river regions of China / Wang Lukun and Azhari Md Hashim - Wang, Lukun; Md Hashim, Azhari (Universiti Teknologi MARA, Kedah, 2023)
China's economic centre gradually moved to the south since the Southern Song Dynasty especially in the Ming and Qing Dynasties. The South Yangtze River Regions of China gradually became the economic, cultural and artistic centre of the whole country. The traditional windows and doors in the South Yangtze River Regions of China were influenced by contemporaneous politics, environment, economy, culture, history, literature and art, which formed unique artistic characteristics. Through the method of documentation investigation, field survey, data analysis and other investigation methods, these artistic characteristics from the aspects of structure, sculpture, colour, pattern, and practicality were summarised based on the analysis of artistic characteristics, consultation of relevant documents, and comparison between traditional architectures and architectural decorations. Through the empirical investigation and interview of traditional Chinese architectural practitioners in related industries, the influencing factors that form these Art Deco features and characteristics were illuminated. The degree of influence of each factor was evaluated, questionnaire surveys of professionals and practitioners were conducted, and the importance of various factors in the formation of their artistic characteristics was quantitatively analysed. The results made it feasible to better understand the differences in the degree of influence of politics, economy, culture, and art in the formation of the artistic characteristics of traditional architectural windows and doors in the South Yangtze River Regions of China.